Pengaruh Tadarrus Alquran Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran Alquran Hadits Di Madrasah Ibtidaiyah Ar-Roja Karangpawitan Garut - Salamudin, Ceceng; Nurdiani, Fitri (STAI Al-Musaddadiyah Garut, 2023)
This research is based on the observed low motivation of students in learning the Alquran Hadits subject at Madrasah Ibtidaiyyah (MI) Ar-Roja Karangpawitan, Garut. This lack of motivation is evidenced by students' reluctance to ask questions and express their opinions during lessons. The practice of Tadarrus Alquran offers a potential solution by fostering a closer connection to the Quran through activities such as reading and listening to its recitations. This closer relationship with the Quran can enhance students' motivation to study it, including in the Alquran Hadits subject. The purpose of this study is to describe the impact of Tadarrus Alquran on students' motivation to learn the Alquran Hadits subject at MI Ar-Roja Karangpawitan Garut. The research employs a descriptive quantitative method. Data collection techniques include observation, interviews, document studies, and questionnaires distributed to 25 respondents. Data processing was conducted through statistical analysis. The results indicate that the motivation of students in the Alquran Hadits subject has an average score of 3.976, which falls within the interval of 3.00 - 4.00, categorizing it as